SIMULASI MISTIK DAN IMPLOSI MAKNA RELIGIUS DALAM SINETRON RAHASIA ILAHI PADA STASIUN TELEVISI TPI - Iswandi Syahputra; Irwan Abdullah; Heru Nugroho; Hermin Indah Wahyuni (Jurnal Ilmu Komunikasi, 2009)
Simulation of mystic in mystical-religious ‘Rahasia Ilahi’ television movie, broadcasted by TPI, is the main focus of this article. Simulation is a thought from Jean Baudrillard (1929- 2007) about production of media text which does not have any reality background. Theoretically, a simulation ended when human, as the subject, has no control over sign, as the object, which in the end, the both merge and turn into a new reality. The merger of the subject and the object mark the emergence of an implosion. Implosion is an inward explosion as a result of the merger of several thoughts through simulation practice. Mystical simulation in ‘Rahasia Ilahi’ television movie could deliver a new and shallow meaning of religious because it had set off from the truth of text and reality as the context. The new meaning could be that the image of God is cruel. There could also be new meaning of religiosity that faith is constructed by fear, not by the truth of the religious thought. Thereby, simulation had become dilemma because it had two meanings. In one side, it is emancipative because it can deliver sharp critics toward the people of television industry who produce television programme which has no reality basis. In the other side, it has negative side because simulation ended with fatalism which is theoretically assumes that subject has no control over object. Pataphysically, this article would like to recommend that subject should return to the power of imagination, rationality, and spirituality. Human as the subject would never loose and cannot be defeated by any object because as khalifah, human should stand in the front line and leading history.